Pengaruh Penggunaan Teknologi Digital dalam Meningkatkan Literasi Digital Siswa Sekolah Dasar - Ananda Putri Kusumawardini; Linda Diah Rifani (Pusat Riset dan Inovasi Nasional, 2021)
This research aims to analyze the influence of the use of digital technology in increasing the digital literacy of elementary school students. Digital literacy is an important ability that students must have in this digital era, including skills in using information and communication technology effectively and responsibly. This research used a quasi-experimental method with a non-equivalent control group design, involving 60 fifth grade students in two elementary schools in City X. Data was collected through digital literacy tests before and after digital technology intervention in learning. The research results show a significant increase in the digital literacy skills of students who use digital technology compared to students who do not use technology in their learning. These findings show the importance of integrating digital technology in the curriculum to develop digital literacy from an early age among elementary school students.